2022
DOI: 10.3390/jcm11030881
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of the Acute PNeumonia Early Assessment Score for Safely Discharging Low-Risk SARS-CoV-2-Infected Patients from the Emergency Department

Abstract: A continuous demand for assistance and an overcrowded emergency department (ED) require early and safe discharge of low-risk severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-infected patients. We developed (n = 128) and validated (n = 330) the acute PNeumonia early assessment (aPNea) score in a tertiary hospital and preliminarily tested the score on an external secondary hospital (n = 97). The score’s performance was compared to that of the National Early Warning Score 2 (NEWS2). The composite outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…This strategy could permit that, with an easily feasible and low-cost test, it is possible to determine the severity and the risk class to which the patient belongs, at least in terms of screening, to direct the patient to the hospital [15]. As some studies have suggested, widespread SpO2 self-monitoring at home (at rest and after walking test) in non-severe COVID-19 could be crucial, reserving anothers testing (blood count, CPR, DDimer, chest X-ray or TC scan) to a more severe disease stage [16,17].…”
Section: N Discussionmentioning
confidence: 99%
“…This strategy could permit that, with an easily feasible and low-cost test, it is possible to determine the severity and the risk class to which the patient belongs, at least in terms of screening, to direct the patient to the hospital [15]. As some studies have suggested, widespread SpO2 self-monitoring at home (at rest and after walking test) in non-severe COVID-19 could be crucial, reserving anothers testing (blood count, CPR, DDimer, chest X-ray or TC scan) to a more severe disease stage [16,17].…”
Section: N Discussionmentioning
confidence: 99%
“…Early and safe discharge of low-risk severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-infected patients is one of the important elements to analyze. A previously defined physiologic score, called aPNea, composed of the alveolar to arterial oxygen (A–A O 2 ) gradient, silent hypoxia diagnosed after a positive 6 min walk test, the importance of lung imaging abnormalities, and the importance of proinflammatory reactions (fever, elevated plasma D-dimer level) compared favorably with traditional severity scores such as NEWS2 (AUC-ROC 0.86 (95% confidence interval (CI), 0.78–0.93)) in predicting a safe hospital discharge from the ED [ 3 ]. Further multicenter validation of the aPNea score in Italy and other countries is needed.…”
Section: Impact Of the Pandemic On The Process Of Hospital Carementioning
confidence: 99%